Molecular causes for the increased stickiness of cooked non-glutinous rice by enzymatic hydrolysis of the grain surface protein. (15th July 2019) - Li, Hongyan; Yang, Jingyuan; Yan, Shu; Lei, Ningyu; Wang, Jing; Sun, Baoguo
Highlights: Soaking non-glutinous rice with protease significantly increased its stickiness. Total solids and amylopectin amount in the leachate are increased by soaking. Molecular size of leached starch is much smaller than that of native starch. Leached amylose CLD is quite different from native amylose CLD. A postulated molecular mechanism is put forward to explain the observations. Abstract: Non-glutinous rice has higher amylose content but less sticky texture than glutinous rice. In this study, by soaking two non-glutinous rice with protease solution, rice stickiness is significantly increased and equivalent to that of glutinous rice. By exploring starch leaching behavior during rice cooking, we find: (i) total solids and amylopectin amount in the leachate are significantly increased by raising the protease concentration during the soaking treatment; (ii) molecular size and chain-length distribution (CLD) of leached starch from these protease-treated rice (PTR) significantly differed from the corresponding native starch; (iii) strong correlations between rice stickiness, amylopectin amount and the proportion of short amylopectin chains with degree of polymerization (DP) <36 in the leachate are established. The possible molecular mechanism for the increased stickiness of treated non-glutinous rice is put forward to explain the above result. This study could broaden the applications of non-glutinous rice for rice industry.